Congenital chylothorax in a preterm infant with non-immune hydrops: A case report with literature review on treatment options - Raya, Ganendra Bhakta; Basnet, Srijana; Nyaupane, Sitaram (Journal of Kathmandu Medical College, 2023)
Congenital chylothorax is rare with an incidence of 1:10,000-24,000 live births. Congenital chylothorax occurs in lymphatic disorders, heart diseases, cancers, chromosomal abnormalities, tracheoesophageal fistula, etc. Acquired causes are due to surgical thoracic duct trauma. Many cases of chylothorax are idiopathic. The case fatality rate is 15% to 57% and reaches 98% in hydrops foetalis. There is no set standard of treatment for congenital chylothorax. Prenatally, thoracentesis or pleuro-amniotic shunts are done. Postnatally, management of cause, drainage, dietary changes, Octreotide, and Sildenafil have variable results. Pleurodesis, pleuroperitoneal shunt, abrasion, thoracic duct ligation, and anastomoses are surgical options.